KONSTRUKSI TINDAK PIDANA BERITA BOHONG (HOAX) DALAM UNDANG-UNDANG ITE - Syaidah Novia Sari (Badamai Law Journal, 2021)
The research aims: 1) To know the construction of hoax criminal acts referred to in the ITE Law. 2) To find out the formulation policy for the future (ius constituentum) in hoax crime. This research is normative legal research. While the type of research is research with emphasis on problems that often arise related to the principle of law with regard to the meaning and scope of criminal acts of hoax in the ITE Law.The results of the study concluded: first, Article 28 paragraph (1) of Law Number 11 of 2008 concerning Information and Electronic Transactions ("ITE Law") as amended by Act Number 19 of 2016 concerning Amendment to Law Number 11 In 2008 concerning Information and Electronic Transactions ("Law 19/2016") stated: Everyone intentionally and without rights spread false and misleading news that resulted in consumer losses in Electronic Transactions. The elements of the crime of spreading false news according to the ITE Law consist of: 1. Everyone, 2. Deliberately and without rights, 3. Spreading false and misleading news, and 4. Which results in consumer losses in electronic transactions. Second, the Government through the Ministry of Communication and Information is more active in building communication with agencies at all levels, so that there are similarities in perspective and resolution in addressing false news (hoaxes) circulating in the community. In order to minimize fake news (hoaxes) circulating on social media, Kominfo must immediately accelerate the pace of coordination with platform providers, be it facebook, twitter, instagram, path, and various other platforms in order to counteract the spread of false news (hoaxes). The meeting with a number of platform providers that have been carried out by the Ministry of Communication and Information is a positive step that must be immediately executed in the form of a written agreement as a legal basis in giving sanctions to platform providers if they deny the agreed agreement. Communication and Information Technology as a representation of state authorities must be brave in expressly regulating how ideally social media operates in Indonesia